Effect of myristic acid of formation of bismuth phosphate nanocrystalline through hot injection method - Nur Liyana Zawawi, 1989-; Lee Siew Ling, supervisor; Fakulti Sains (2010)
Project paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011